CHANGES IN MATHEMATICAL OLYMPIAD PROBLEM SETS IN LATVIA - Avotina, Maruta; Šuste, Agnese (Acta Paedagogica Vilnensia, 2015)
Students’ average results in mathematical olympiads in Latvia are quite low, and this is a signal that something is not right. To improve students’ results and motivation, in the last two years some changes were made in the Olympiad problem set. Our goal is to investigate how these changes affected students’ average results and attitude towards mathematical olympiads. In the paper, we describe changes that were made to the mathematical olympiad problem set, consequences and conclusions.
Keywords: mathematical olympiads; problem set; “repeated” problem; “topic” problem; “school level” problem; students results